Basal protein synthesis rates differ between vastus lateralis and rectus abdominis muscle. Issue 3 (5th May 2021) - Smeets, Joey S.J.; Horstman, Astrid M.H.; van Dijk, David P.J.; van Boxtel, Astrid G.M.; ter Woorst, Joost F.; Damink, Steven W.M. Olde; Schijns, Olaf E.M.G.; van Loon, Luc J.C.
Abstract: Background: In vivo muscle protein synthesis rates are typically assessed by measuring the incorporation rate of stable isotope labelled amino acids in skeletal muscle tissue collected from vastus lateralis muscle. It remains to be established whether muscle protein synthesis rates in the vastus lateralis are representative of muscle protein synthesis rates of other muscle groups. We hypothesized that post‐absorptive muscle protein synthesis rates differ between vastus lateralis and rectus abdominis, pectoralis major, or temporalis muscle in vivo in humans. Methods: Twenty‐four patients (62 ± 3 years, 42% female), scheduled to undergo surgery, participated in this study and underwent primed continuous intravenous infusions with l ‐[ring‐ 13 C6 ]‐phenylalanine. During the surgical procedures, serum samples were collected, and muscle tissue was obtained from the vastus lateralis as well as from the rectus abdominis, pectoralis major, or temporalis muscle. Fractional mixed muscle protein synthesis rates (%/h) were assessed by measuring the incorporation of l ‐[ring‐ 13 C6 ]‐phenylalanine into muscle tissue protein. Results: Serum l ‐[ring‐ 13 C6 ]‐phenylalanine enrichments did not change throughout the infusion period. Post‐absorptive muscle protein synthesis rates calculated based upon serum l ‐[ring‐ 13 C6 ]‐phenylalanine enrichments did not differ between vastus lateralis and rectus abdominis (0.032 ± 0.004 vs. 0.038 ± 0.003%/h), vastus lateralis and pectoralis major, (0.025 ± 0.003 vs. 0.022 ± 0.005%/h) or vastus lateralis and temporalis (0.047 ± 0.005 vs. 0.043 ± 0.005%/h) muscle, respectively ( P  > 0.05). When fractional muscle protein synthesis rates were calculated based upon tissue‐free l ‐[ring‐ 13 C6 ]‐phenylalanine enrichments as the preferred precursor pool, muscle protein synthesis rates were significantly higher in rectus abdominis (0.089 ± 0.008%/h) compared with vastus lateralis (0.054 ± 0.005%/h) muscle ( P  < 0.01). No differences were observed between fractional muscle protein synthesis rates in vastus lateralis and pectoralis major (0.046 ± 0.003 vs. 0.041 ± 0.008%/h) or vastus lateralis and temporalis (0.073 ± 0.008 vs. 0.083 ± 0.011%/h) muscle, respectively. Conclusions: Post‐absorptive muscle protein synthesis rates are higher in rectus abdominis when compared with vastus lateralis muscle. Post‐absorptive muscle protein synthesis rates do not differ between vastus lateralis and pectoralis major or temporalis muscle. Protein synthesis rates in muscle tissue samples obtained during surgery do not necessarily represent a good proxy for appendicular skeletal muscle protein synthesis rates.